2022
DOI: 10.3390/cells11030470
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Primed Mesenchymal Stromal Cells Loaded on Biphasic Calcium Phosphate Biomaterial Exhibit Enhanced Macrophage Polarization

Abstract: Mesenchymal stromal cells (MSC) loaded on biphasic calcium phosphate biomaterial (MSC + BCP) have been used as an advanced therapy medicinal product to treat complex maxillofacial bone defects in patients. Further, MSC-derived extracellular vesicles (EVs) are established vehicles of paracrine factors, supporting inter-cellular communication between MSC and other interacting cell types, such as monocytes/macrophages. However, the information about the immunomodulatory potential of EVs derived from MSC and bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…They can be categorised into different subtypes based on their size or biogenesis mode, that is, exosomes (30–150 nm), microvesicles (100–1000 nm) and apoptotic bodies (1000 nm–5 μm). In the absence of specific markers and overlapping sizes, the term “small EVs” (sEVs) applies to both exosomes and microvesicles up to 200 nm in size and “medium and/or large EVs” (m/lEVs) refers to >200 nm in size (Rana et al., 2022 ; Théry et al., 2018 ). Different species use various names for extracellular vesicles (EVs), including EVs‐like nanovesicles, exosome‐like extracellular vesicles and exosome‐like nanovesicles (ENVs).…”
Section: Resultsmentioning
confidence: 99%
“…They can be categorised into different subtypes based on their size or biogenesis mode, that is, exosomes (30–150 nm), microvesicles (100–1000 nm) and apoptotic bodies (1000 nm–5 μm). In the absence of specific markers and overlapping sizes, the term “small EVs” (sEVs) applies to both exosomes and microvesicles up to 200 nm in size and “medium and/or large EVs” (m/lEVs) refers to >200 nm in size (Rana et al., 2022 ; Théry et al., 2018 ). Different species use various names for extracellular vesicles (EVs), including EVs‐like nanovesicles, exosome‐like extracellular vesicles and exosome‐like nanovesicles (ENVs).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, compared with Plate‐CM one, SS‐CM group increased gene expression of osteogenic markers such as ColI and Bsp on day 3, Runx2 , Osx and Alp on day 7, which was in agreement with our previous study, indicating that BCP ceramics could induce macrophages toward M2 phenotype to release a mass of anti‐inflammatory cytokines and growth factors, which could reduce inflammation and provide a local inflammatory microenvironment suitable for osteogenesis. [ 54,55 ] VS‐CM group not only showed the highest ALP activity and osteogenic gene expression (i.e., Runx2 , ColI , Bmp2 , Alp , Bsp and Osx ) in vitro, but also significantly up‐regulated the expression of osteogenic genes in vivo, including the early osteogenic markers like Bmp‐2 and Alp , and the late osteogenic markers like Ocn and Opn . A nude mice subcutaneous implantation model found that VS‐CM group promoted the early bone formation, as evidenced by the accelerated formation of collagen‐rich osteoid‐like tissues and the highest expression of osteogenic marker (BMP‐2).…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentration of EV samples was measured by Pierce™ BCA Protein assay kit (Thermo Fisher Scientific, USA), following the manufacturer’s instructions. EVs morphology was recorded by transmission electron microscopy (TEM), according to a previously described protocol [ 24 ]. The final EV preparations were examined using a Jeol JEM1400 transmission electron microscope (Jeol Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%